The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.3390/ijms18010118
|View full text |Cite
|
Sign up to set email alerts
|

Role of IRE1α/XBP-1 in Cystic Fibrosis Airway Inflammation

Abstract: Cystic fibrosis (CF) pulmonary disease is characterized by chronic airway infection and inflammation. The infectious and inflamed CF airway environment impacts on the innate defense of airway epithelia and airway macrophages. The CF airway milieu induces an adaptation in these cells characterized by increased basal inflammation and a robust inflammatory response to inflammatory mediators. Recent studies have indicated that these responses depend on activation of the unfolded protein response (UPR). This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 163 publications
3
41
0
Order By: Relevance
“…For example, raised levels of IL-17 were not found in the CF patients in contrast to prior studies including young children [7][8][9]. The role of the UPR in CF remains unclear, with some studies implicating a direct effect of F508del misfolding while others find key UPR inducers come indirectly from the inflammatory milieu that may be variably induced by the many pathogens capable of transiently or chronically infecting the CF airway [5], or even by sterile inflammation prior to infection. The role of impaired autophagy implicated in CF on sIgA remains unexplored.…”
mentioning
confidence: 77%
“…For example, raised levels of IL-17 were not found in the CF patients in contrast to prior studies including young children [7][8][9]. The role of the UPR in CF remains unclear, with some studies implicating a direct effect of F508del misfolding while others find key UPR inducers come indirectly from the inflammatory milieu that may be variably induced by the many pathogens capable of transiently or chronically infecting the CF airway [5], or even by sterile inflammation prior to infection. The role of impaired autophagy implicated in CF on sIgA remains unexplored.…”
mentioning
confidence: 77%
“…Based on the effect of ACE-2/ANG1-7, we tried to design a targeted treatment method that makes ACE-2/ANG1-7 work only in damaged or preapoptotic cells. In the process of ER stress, phosphorylation of IRE1 can splice XBP1u mRNA to XBP1s mRNA, which can encode XBP1s protein in a short period of time (21). XBP1s has almost no expression in normal lung tissues and seawater stimulation activated the expression of p-IRE1/XBP1s in damaged cells.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate this issue, we analyzed the effect of iPA on IL-8 and RANTES release in CuFi-1 (CFTR ΔF508/ΔF508 ) and NuLi-1 cell lines (CFTR wild type) which are both telomerase-immortalized airway cells, characterized by the ability to constitute a polarized monolayer with a transepithelial activity that mimics the behavior of CF airway epithelial cells in vivo [ 20 ]. CuFi-1 cells show overexpression of a number of signal transduction pathways including MAPK/ERK and NFκB that are responsible for the overactivation of several inflammatory and oxidative stress genes such as IL-6, IL-8 and RANTES [ 33 , 34 ]. The use of these two cell systems allowed us to ascertain whether the effect of iPA was related to the CFTR mutation or was a common anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in agreement with Dassano et al [ 32 ] who showed that in breast cancer and HL-60 cells induced to differentiate in neutrophilic lineage, iPA was able to trigger the NRF-mediated oxidative response through the induction of gene encoding detoxifying and anti-oxidant enzymes—such as heme oxygenase-1 gene and glutamate-cysteine ligase (GCLC)—that protect cells against ROS and reactive metabolites. In conclusion, as airway epithelial cells contribute significantly to airway inflammation in patients with CF [ 34 , 36 ]. The fine tuning of cyto-chemokines secretion by iPA along with its ability to improve selenoprotein expression might be an attractive therapeutic approach to reduce excessive airway inflammation which is a major cause of CF morbidity.…”
Section: Discussionmentioning
confidence: 99%